Faktory ovlivňující výskyt vodních makrofyt v nádrži Lipno - Krolová, Monika (Jihočeská univerzita, 2013)
This RNDr. thesis focuses on the species composition and cover in the littoral of the Lipno Reservoir in 2006. Aquatic macrophytes are an essential component of littoral communities in lakes. Their reasonable development positively affects biodiversity and stability of the aquatic ecosystems and water quality. The aim of this study was to characterise the development of littoral macrophytes in Lipno Reservoir, an artificial lake with seasonal water level fluctuation, and highlight controlling factors for macrophyte occurrence. The development of macrophytes was examined at 114 segments of the shoreline, each 50 m long, situated along the whole reservoir perimeter in regular 1km distances. The segments were surveyed for phytocenology, shore morphology, pedological characteristics of substrate, and anthropogenic impact. The survey identified 53 macrophyte species (24 hydrophilic terrestrial, 17 emergent,1 floating-leaved, 2 free-floating, 4 submersed, and 5 amphibious). The average vegetation cover of the examined segments was 14 %, with approximately one third of the segments without any macrophytes and another third with vegetation cover less than 10 %. Macrophytes occurred only in the uppermost eulittoral zone down to the level of 75 % probability of water surface exceedance. On the basis of a correlation analysis, the major factors affecting macrophyte occurrence in the littoral zone were shore morphology, light conditions in water and erosion effect of waves that together with water level fluctuation caused loss of fine particles from and degradation of the substrate in the littoral zone.
Factors affecting the occurrence of aquatic macrophytes in the Lipno reservoir
Keywords: littoral vegetation; littoral morphology; vegetation cover; erosion effect of waves; water level fluctuation; grain size distribution of substrate